UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN STAD - Musriah Musriah (STKIP PGRI Tulungagung, 2019)
This research is aimed to improve mathematics students learning outcomesin elementary school, especially on folding symmetry and rotary symmetry materials throughthe implementation of cooperative learning on STAD. This research was a classroom action research refferedto Kemmis and Mc Taggart design, which includes planning, acting, observing, and reflecting. The research subject were all the student of fifth grade in SDN 1 Ketajen Gedangan Sidoarjo in the the period of 2017/2018. After the action is applied, average value in the test resultson cycle I is 61,66 while average value in the test resultson cycle II is 70.